Empowering minds, body and soul: An evaluative case-study of the perceptions of the extent of women empowerment within a Higher Certificate in Education in Adult Education course at UCT - Kibido, Princess Fundiswa (School of Education, 2022)
The Adult Education sector in South Africa (SA) occupies a crucial space in higher education (HE) in terms of securing access and opportunities for a diverse group of non-traditional students to further their development. Amongst this diversity are highly marginalized subgroupings of adult learners, especially black working-class women. Participation of these women within HE requires serious attention given the low social ranking that this group continues to occupy in all spheres. Evidence drawn from Adult Education research suggests that not enough attention has been given to this group of learners with respect to how they are impacted by issues of geographic, cultural and racial diversity in the Adult Education setting. This study undertaken here reports on transformative dimensions underlining Adult Education pedagogy, with a specific focus on the concept of empowerment and how this is attained by RPL learners. A qualitative case-study methodology using a critical interpretive perspective grounded in phenomenological enquiry, was used to develop contextual understandings of four disadvantaged adult female learners' experiences of their transitions into HE. The focus is on these learners' perceptions of the forms of empowerment they have gained from their participation in a Higher Certificate in Education in Adult Education (HCEAE) course, and the extent to which such empowerment has impacted positive change in their lives, even beyond the course. The argument made in this qualitative study is that the active participation of marginalized black women in Adult Education, does lead to the attainment of multiple levels of self-empowerment. Such empowerment is realized when the objectives of national educational provisions, operationalized through Adult Education legislature, are correctly aligned with the transformative and social justice mission of Adult Education theory and practice. Proper alignment yields desirable outcomes in terms of enabling transformative learning environments that engender experiences of self-empowerment, agency and control. To this effect, an evaluative study was conducted of the Higher Certificate in Education in Adult Education (HCEAE) course offered by the University of Cape Town. The findings in this study demonstrate that factors such as race, geographic setting and cultural location, impact experiences of empowerment amongst adult learners. Furthermore, it is evident that such experiences of empowerment is a multi-layered and dynamic process which occur at cognitive, personal and social levels that can only be realized through praxis. The bringing together of educational policy, theory, and practice in proactive and productive ways in this study, also offers the potential for designing new hybrid frameworks for assessing the extent to which Adult Education provisions successfully achieve their transformative function, beyond the educational setting.